ASSOCIAÇÃO DA CONDIÇÃO PERIAPICAL COM OUTRAS ALTERAÇÕES RADIOGRÁFICAS. - VELOSO, Suzanni do Amaral Rodrigues (2007)
The goal of the present work is to correlate different levels of apical periodontitis (AP) with radiographic signs such as: crown decay, presence of crown, endodontic treatment, distance from the end of the root canal filling to radiographic apice, assembly of restorative material, presence of external resorption and presence of intra-radicular post and its distance to the radiographic apice. A population of 300 cases with apical periodontitis collected from orthodontic offices. A total of 159 (53%) males and 141 (47%) females with ages ranging from 20 to 45 were used in this study. The apical condition was radiographically determined by means of the Apical Periodontitis Indice (API). The data were analyzed statistically using the chi-squared test. In relation to the age, greatest frequency of cases ranged between 26 to 30 years old (20,67%) and 36 to 40 (23%). The greatest incidence of AP was in first lower molars (21,3%), followed by upper incisor (17%) and second lower molars (13,7%). The results showed an association of AP and factors like, distance from the root canal filling to the apice (p<0.0001), assembly of the restorative material (p<0.0001), external resorption (p<0.0001) and distance from the intra-radicular post to the radiographic apice (p<0.0001). However, no significant difference was detected in relation to age, sex, coronal filling and decay.